2013
DOI: 10.1134/s000629791313004x
|View full text |Cite
|
Sign up to set email alerts
|

AGR2, ERp57/GRP58, and some other human protein disulfide isomerases

Abstract: This review considers the major features of human proteins AGR2 and ERp57/GRP58 and of other members of the protein disulfide isomerase (PDI) family. The ability of both AGR2 and ERp57/GRP58 to catalyze the formation of disulfide bonds in proteins is the parameter most important for assigning them to a PDI family. Moreover, these proteins and also other members of the PDI family have specific structural features (thioredoxin-like domains, special C-terminal motifs characteristic for proteins localized in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 129 publications
0
21
0
2
Order By: Relevance
“…Therefore, through bioinformatics analysis and molecular biology validation, we found that miR‐3647‐5p can target the 3′UTR of AGR2 and inhibit the expression of AGR2. AGR2 is a protein disulfide isomerase . Studies have found that compared to normal pancreatic tissues, the expression of AGR2 is up‐regulated in benign pancreatic lesions, low‐grade and high‐grade tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, through bioinformatics analysis and molecular biology validation, we found that miR‐3647‐5p can target the 3′UTR of AGR2 and inhibit the expression of AGR2. AGR2 is a protein disulfide isomerase . Studies have found that compared to normal pancreatic tissues, the expression of AGR2 is up‐regulated in benign pancreatic lesions, low‐grade and high‐grade tumors .…”
Section: Discussionmentioning
confidence: 99%
“…AGR2, also known as PDIA17, XAG‐2, hAG‐2, an ER‐resident protein mainly expressed in human epithelial cells, was assigned to the human Protein Disulphide Isomerase (PDI) family later than all other members [Shishkin et al., ]. The PDI family has 21 proteins that are involved in numerous physiological and pathological processes [Shishkin et al., ]. PDI proteins have an important structural feature in common, one or several thioredoxin‐like domains and also similar intracellular localisation – in the ER and/or in other membrane formations.…”
Section: Agr2 and The Tnsmentioning
confidence: 99%
“…ERp57 is a member of the protein disulfide isomerase family that is mainly located in the endoplasmic reticulum, and has well-characterized functions as a cellular protective protein [ 31 , 32 , 53 ]. It participates in the quality control of newly synthesized glycoproteins, in association with calnexin/calreticulin, and is also an important component of the major histocompatibility complex class I peptide loading complex [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we focused the present study on investigating the ability of LEDGF/p75 to protect PCa cells against oxidative stress-induced necrosis, and contribute to the upregulation of endoplasmic reticulum protein of 57 kD (ERp57) in PCa. ERp57, also known as glucose regulated protein of 58 kD (GRP58) and protein disulfide isomerase family A member 3 (PDIA3), is a multi-functional thiol-oxidoreductase and a chaperone protein responsible for maintaining the appropriate folding of newly synthetized glycoproteins [ 31 , 32 ]. Our results indicate that LEDGF/p75 overexpression attenuates oxidative stress-induced necrotic cell death and contributes to ERp57 upregulation in the context of PCa.…”
Section: Introductionmentioning
confidence: 99%